Koreksi Panjang Kerja pada Perawatan Saluran Akar Gigi 21 yang Optimal - Rahmah, Siti; Nurdin, Denny (Bhakta Dental Journal, 2024)
Determining the working length is one of the first and most important steps in root canal treatment. Determining the working length can use the electronic apex locator method and periapical radiographs.Case: A 25-year-old female patient came to Unpad Dental Hospital with complaints of left upper filling pain when eating hard food since 1 year ago. The patient complained that there was a history of spontaneous pain. Based on the results of history and examination, the patient was diagnosed with previously initiated therapy with symptomatic apical periodontitis in tooth 21. Treatment plan in the form of root canal treatment (RCT) in tooth 21. Management: root canal treatment begins with access opening and removal of temporary fillings, crown down preparation, measurement of working length using apex locator, trial obturation, working length correction, obturation. Conclusion: The working length measurement method with the combination of electronic apex locator and periapical radiography is very helpful in correcting improper working length. Keywords: Working length, Root canal treatment, Electronic apex locator, Radiography